Impact of area strain by 3D speckle tracking on clinical outcome in patients after acute myocardial infarction. Issue 12 (25th August 2016) - Shin, Sung‐Hee; Suh, Young Ju; Baek, Yong‐Soo; Lee, Man‐Jong; Park, Sang‐Don; Kwon, Sung‐Woo; Woo, Seong‐Ill; Kim, Dae‐Hyeok; Park, Keum‐Soo; Kwan, Jun
Abstract : Background: Three‐dimensional (3D) speckle tracking echocardiography (STE) has been developed to overcome the limitations of two‐dimensional (2D) STE and has been applied in the several clinical settings. However, no data exist about the prognostic value of 3DSTE‐based strain on clinical outcome after myocardial infarction (MI). This study was designed to investigate the prognostic value of area strain (AS) by 3D speckle tracking in predicting clinical outcome after acute MI. Methods: We assessed 96 patients (62±14 years, 72% male) with acute MI and who had undergone a coronary angiography. Clinical parameters and conventional echocardiographic measurements including the left atrial (LA) size and tissue Doppler measurements were evaluated. The global left ventricular (LV) AS was measured using 3D speckle tracking software. The relationship between the AS and clinical outcome of death or hospitalization for heart failure (HF) was assessed. Results: During a median follow‐up of 33±10 months, primary endpoint of death or HF occurred in 12 patients (12.5%). AS was predictive of death or HF after adjustment for age, gender, peak CK‐MB, LA volume, LV end‐systolic volume, LV mass, the ratio of early mitral inflow velocity to early mitral annular velocity, and LV ejection fraction in a multivariate Cox model (HR 1.23, 95% CI 1.02–1.47, P =.03). In addition, AS added incremental value in predicting death or heart failure on a model based on clinical and standard echocardiographic measures ( P =.008). Conclusion: AS is independently associated with increased risk of death or HF after acute MI, suggesting that it can be a useful prognostic parameter in the patients following MI.